Co-metabolic Effect of Glucose on Methane Production and Phenanthrene Removal in an Enriched Phenanthrene-Degrading Consortium Under Methanogenesis - Zhou, Ziyan; Wang, Yanqin; Wang, Mingxia; Zhou, Zhifeng (Frontiers in Microbiology, 2021)
Anaerobic digestion is used to treat diverse waste classes, and polycyclic aromatic hydrocarbons (PAHs) are a class of refractory compounds that common in wastes treated using anaerobic digestion. In this study, a microbial consortium with the ability to degrade phenanthrene under methanogenesis was enriched from paddy soil to investigate the cometabolic effect of glucose on methane (CH4) production and phenanthrene (a representative PAH) degradation under methanogenic conditions. The addition of glucose enhanced the CH4 production rate (from 0.37 to 2.25 mgL-1d-1) but had no influence on the degradation rate of phenanthrene. Moreover, glucose addition significantly decreased the microbial -diversity (from 2.59 to 1.30) of the enriched consortium but showed no significant effect on the microbial community (R2 = 0.39, P = 0.10), archaeal community (R2 = 0.48, P = 0.10), or functional profile (R2 = 0.48, P = 0.10). The relative abundance of genes involved in the degradation of aromatic compounds showed a decreasing tendency with the addition of glucose, whereas that of genes related to CH4 synthesis was not affected. Additionally, the abundance of genes related to the acetate pathway was the highest among the four types of CH4 synthesis pathways detected in the enriched consortium, which averagely accounted for 48.24% of the total CH4 synthesis pathway, indicating that the acetate pathway is dominant in this phenanthrene-degrading system during methanogenesis. Our results reveal that achieving an ideal effect is diffcult via co-metabolism in a single-stage digestion system of PAH under methanogenesis; thus, other anaerobic systems with higher PAH removal efficiency should be combined with methanogenic digestion, assembling a multistage pattern to enhance the PAH removal rate and CH4 production in anaerobic digestion.